Digital Image DNA Cytometry: A Useful Tool for the Evaluation of Malignancy in Biliary Strictures - M. C. Osterheld; S. Andrejevic Blant; L. Caron; R. Braunschweig; G. Dorta; H. Bouzourene; A. Mihaescu (Cellular Oncology)
Background: Cytologic evaluation of the biliary tract strictures is nowadays widely used for distinguishing between benign and malignant lesions but remains a challenge for some problematic cases. Digital Image cytometry (DNA-cytometry) helps cytopathologists to resolve some unclear situations.